1995
DOI: 10.1159/000126810
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Estrogen Receptor-Immunoreactive Cells in Monkey Hypothalamus: Relationship to Neurones Containing Luteinizing Hormone-Releasing Hormone and Tyrosine Hydroxylase

Abstract: The precise sites and mechanisms by which gonadal steroids influence the activity of neuroendocrine cells controlling pituitary hormone secretion are poorly understood. The present study has determined the distribution of estrogen receptor (ER)-immunoreactive cells in the monkey hypothalamus and examined whether ERs are expressed by luteinising hormone-releasing hormone (LHRH)-and/or dopamine-containing neurones. The distribution of ER-immunoreactive cells was determined in ovariectomised (n = 2) and estrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 21 publications
4
43
0
Order By: Relevance
“…In conjunction with the observation that GnRH neurons do not possess classical steroid receptors (11)(12)(13)(14)(15), these findings suggest that the surge-inducing estradiol signal is transmitted indirectly to the GnRH neurosecretory system through a series of one or more interneurons. Progesterone is known to block the ability of estradiol to stimulate a preovulatory GnRH/LH surge (10), but whether progesterone blocks activation of the system by estradiol, the activity of the interneurons involved in signal transmission or GnRH secretion itself, remains unknown.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In conjunction with the observation that GnRH neurons do not possess classical steroid receptors (11)(12)(13)(14)(15), these findings suggest that the surge-inducing estradiol signal is transmitted indirectly to the GnRH neurosecretory system through a series of one or more interneurons. Progesterone is known to block the ability of estradiol to stimulate a preovulatory GnRH/LH surge (10), but whether progesterone blocks activation of the system by estradiol, the activity of the interneurons involved in signal transmission or GnRH secretion itself, remains unknown.…”
Section: Discussionmentioning
confidence: 72%
“…Eight ewes were exposed to four treatments, over successive artificial estrous cycles. Positive and negative controls were similar to those described in Study 1, except the duration of the stimulatory estradiol signal was reduced to 8 h. The two experimental groups consisted of an EARLY P (progesterone) treatment, in which progesterone was given from hours 8 -13 after estradiol insertion (immediately after estradiol removal), and a LATE P treatment, in which progesterone was given from hours [13][14][15][16][17][18] (immediately before LH surge secretion). As expected, LH surges were stimulated and blocked, in response to the positive and negative controls, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In adult animals, gonadal steroids inhibit LH secretion by decreasing the activity of neurons in the mediobasal hypothalamus (O'Bryne et al 1993), resulting in a decrease in LHRH biosynthesis (Toranzo et al 1989) and release (Karsch et al 1987). Since LHRH neurons do not contain estrogen receptors, these inhibitory effects of estradiol on LHRH biosynthesis and release are complex and probably involve an interneuronal pathway (Herbison et al 1995, Sullivan et al 1995, possibly the activation of the inhibitory neurotransmitter -aminobutyric acid (GABA) in discrete hypothalamic neurons (Herbison et al 1991, McRee & Meyer 1993. The expression of estrogen receptors on GABAergic and glutamate neurons increases developmentally in female monkeys (Thind & Goldsmith 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In the brain, gonadotropin-releasing hormone (GnRH) is the primary upstream regulator of reproductive function and it is well accepted that testosterone and estradiol exert tight control over the negative feedback pathways that regulate GnRH synthesis and release. However, since initial efforts aimed at detecting AR and ER in GnRH neurons failed (Huang andHarlan, 1993, Shivers et al, 1983),, many investigators concluded that the effects of steroid hormones on GnRH were mediated indirectly (Herbison et al, 1995;Herbison and Theodosis, 1992;Lehman and Karsch, 1993). However, the identification of ERbeta resurrected this longstanding hypothesis, as several laboratories subsequently showed the co-expression of GnRH and ERβ (Hrabovszky et al, 2000;Hrabovszky et al, 2001;Kallo et al, 2001;Skynner et al, 1999).…”
Section: Other Roles For 3beta -Diol In Brain Functionmentioning
confidence: 99%